Analysis of Take Over Financing With Reference To DSN-MUI Fatwa No.31/DSN-MUI/VI/2002 Concerning Hiwalah and DSN-MUI Fatwa No.31/DSN-MUI/VI/2002 Concerning Debt Transfer (Case Study at BSI KCP Sigli Madjid Ibrahim) - Muhammad Kharazi; Saparuddin Saparuddin; Sugianto Sugianto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this research is to determine the implementation of take over financing at BSI KCP Sigli Madjid Ibrahim and its relevance to the DSN-MUI fatwa No.31/DSN-MUI/VI/2002 regarding hiwalah and DSN-MUI fatwa No.31/DSN-MUI/ VI/2002 regarding debt transfer. The research method used in this research is field research. This research is also included in the category of qualitative descriptive research. The results of the research show that in applying for take over financing at BSI KCP Sigli Madjid Ibrahim, the customer submits a debt transfer request, fills out a form, then analyzes and surveys. After it was approved, then the BSI KCP Sigli Madjid Ibrahim used the al-qardh wa al-murabahah contract and also the al-qardh wa al-ijarah al-muntahiyah bi al-tamlik contract. Then the disbursement of financing funds was made by the BSI KCP Sigli Madjid Ibrahim to pay off the remaining customer debt at the previous bank. The implementation of take over financing at BSI KCP Sigli Madjid Ibrahim in the settlement of debt transfers is in accordance with the DSN-MUI fatwa.